Socioeconomic school segregation in Canary Islands - Prieto-Latorre, Claudia; Marcenaro-Gutiérrez, Óscar David (Taylor & Francis, 2021)
This study provides evidence about the degree of socioeconomic segregation in Spain’s primary schools. In particular, the analysis is based on data from Canary Islands, a Spanish region with low level of academic performance and high level of students enrolled in fully public schools. The approach used to study school segregation deepens on the contribution of the type of school funding to the overall school segregation, which is addressed using the Hutchens Index. Results suggests that differences between fully state-funded schools and private schools account for 20-30% of the total level of segregation.
Keywords: Discriminación en la enseñanza; school segregation; socioeconomic status; Hutchens Index; public schools; private schools